The Evolution of the Physician Role in the Setting of Increased Non-physician Clinicians in Sub-Saharan Africa: An Insistence on Timing and Culturally-Sensitive, Purposefully Selected Skill Development; Comment on "Non-physician Clinicians in Sub-Saharan Africa and the Evolving Role of Physicians" - Agnes Binagwaho; Gabriela Sarriera; Arielle Eagan (Kerman University of Medical Sciences, 2017)
As Eyal et al put forth in their piece, Non-physician Clinicians in Sub-Saharan Africa and the Evolving Role of Physicians, task-shifting across sub-Saharan Africa through non-physician clinicians (NPCs) has led to an improvement in access to health services in the context of physician-shortages. Here, we offer a commentary to the piece by Eyal et al, concurring that physician's roles should evolve into specialized medicine and that skills in mentorship, research, management, and leadership may create more holistic physicians clinical services. We believe that learning such non-clinical skills will allow physicians to improve the outcome of their clinical services. However, at the risk of a local, clinical brain drain as physicians shift to explore beyond the clinical sphere, we advocate strongly for increased caution to be exercised by leadership over the encouragement of this evolution. In the context of still-present physician shortages across many developing countries, we advocate to analyze this changing role and to purposefully select each new skill according to the context, giving careful consideration to the timing and degree of its evolution.